2020
DOI: 10.1177/0891242420921451
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Property Tax Abatements on School District Property Tax Bases and Rates

Abstract: The authors analyze the effects of property tax abatement on the property tax base and rates of school districts within a municipality offering the abatement using data from Franklin County, Ohio, one of the most populous counties in the United States. An increase in a school district’s Community Reinvestment Area abatement intensity correlates with (a) a decrease in the mill rate for real property, (b) a decrease in effective residential and nonresidential property tax rates, and (c) an increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Weber (2003) found that the use of tax increment financing (TIF) in Cook County, Illinois hampers revenue growth for school districts and increases their dependence on state aid. Using panel data, Kenyon et al (2020) found that in Franklin County, Ohio, the increase in taxable value resulting from tax abatements in the county is matched by a decrease in the tax rate. Wendling (1981) found that Michigan's Public Act 198 exemptions hurt school districts that are just off the state aid formula.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Weber (2003) found that the use of tax increment financing (TIF) in Cook County, Illinois hampers revenue growth for school districts and increases their dependence on state aid. Using panel data, Kenyon et al (2020) found that in Franklin County, Ohio, the increase in taxable value resulting from tax abatements in the county is matched by a decrease in the tax rate. Wendling (1981) found that Michigan's Public Act 198 exemptions hurt school districts that are just off the state aid formula.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Initial education litigation tackled discrimination and disparities for disadvantaged children. 77 These discrimination lawsuits laid important groundwork for addressing the numerous faults in the public education system. 78 In Brown v. Board of Education, the United States Supreme Court unanimously ruled that racial segregation violated the Equal Protection Clause of the Fourteenth Amendment.…”
Section: A Education Litigation In the United Statesmentioning
confidence: 99%
“…School districts use property tax base to set property tax rates. All else being equal, a higher TIF-induced property tax base, as reported later, may induce them to provide relief for residents by reducing property tax rates (Kenyon et al, 2020). Alternatively, school districts may not adjust property tax rates.…”
Section: Introductionmentioning
confidence: 99%